Faktor-Faktor Ketidakhadiran Wali Adhal dalam Pernikahan: Studi Kasus Konflik Keluarga dan Status Pekerjaan - Iqbal Adam Pradana; Riyan Erwin Hidayat; Dri Santoso; Dedy (Bulletin of Community Engagement, 2024)
The absence of a guardian in a marriage is the main conflict experienced by the prospective bride and groom when they are about to carry out a marriage, where a guardian is one of the conditions for the validity of a marriage. So that without a guardian, a marriage is considered not to fulfill the requirements in Islamic law. There are several factors behind it. The absence of a guardian at a marriage includes the problem of conflict between the two families, and the factor of unclear or permanent employment status which then becomes the main problem of the absence of a guardian at a marriage. The factors above are the most significant cases of guardian cases in the last five years. This is in court Religion. In this research, the aim of the researcher is to answer the problems that occur in guardian cases. Regarding the factors that most influence guardians' reluctance to marry off their children, using a field research method which is descriptive in nature, then analyzed qualitatively using a juridical approach to the decision of the panel of judges. religious court regarding the application for guardian adhal. The data sources from this research are primary data sources and secondary data. Which was collected directly through the religious court where the research was conducted. With the findings, there were five cases from 2O19 until now with cases due to the factors above.